Integration of e-commerce, information technology and its impact on reducing costs to make pricing decisions - عبد عبد خلف; النعيمي نادية شاكر (Journal of Economics and Administrative Sciences, 2018)
E-commerce is the most important result of information technology in this day and age, has resulted in the use of commercial transactions to changes in economic, social, and psychological, and produced a new type of shopping, jobs, and create new job opportunities, and changed the traditional work environment. The challenge currently facing economic units is how to transfer this technology and its integration within the community, especially after the massive developments that have occurred in the areas of commercial and congested markets units, the economic and the products and services the many and varied and intensified competition among these units to achieve a profit, leading to the emergence of e-commerce as one of the means of modern trade which has affected and dramatically change the future of the business and initiated through what made possible by means of information technology to facilitate the buying and selling process electronically, which led to increase the efficiency of the performance of economic units and strengthen the competitive position of her, also contributed through its vital role in the marketing of products and services that Units electronically to facilitate the process of obtaining those products and services by customers and within the area of ​​geographical area and wide at the time and the speed limit and reduce the cost of marketing products and services for those units to a minimum, so it will be highlighted in this paper on the importance of e-commerce, information technology and the impact of integration with each other in reducing both the cost of producing goods and services and the costs of marketing and reflection so effective when adopted by the economic units in the rationalization of pricing decisions to achieve customer satisfaction and meet the desires and in the last analysis to strengthen the competitive position of those units in the business environment in line with the challenges of successive in all areas performance of information technology in today’s world.